COLORIMETER DESIGN FOR COLOR DETECTION OF DROPLET AND ITS IMPLEMENTATION IN DETERMINING GLUCOSE CONCENTRATION - I T Kertasafari, Najmi
Measurement of blood glucose is crucial for maintaining body condition, especially for individuals with diabetes mellitus. One way to determine blood glucose level is by conducting Benedict’s test, where sample solution is dissolved with Benedict’s reagent, causing the solution to change color according to the glucose content. However, color observation is still commonly done manually, meaning it is only observed with naked eye. This can lead to human errors due to variation in color perception among individuals and lack of consistency due to subjective measurements. Measurement error can result in misdiagnosis. Therefore, a measuring instrument is needed to provide accurate and consistent color measurement. As a solution, the author designed a colorimeter capable of detecting the color of a droplet resulting from the mixing process in the Digital Microfluid system. The system works by capturing image of the sample passing through the constant light and then processing the image to obtain the HSV values of the droplet. The system utilizes a Raspberry Pi Zero W microprocessor, a Raspberry Pi Camera V2 digital camera, and an LCD touchscreen as the user interface. The system is programmed using the OpenCV library in Python.